Wuqinxi exercise for mind and balance: Enhancing cognition, fall prevention, and quality of life in older adults with mild cognitive impairment - Qingpan Wen; Shiying Chen; Huan Zhou; Yangjun Liu; Jianye Li; Marcin Białas; Dominika Wilczyńska (PLoS ONE, 2026)
Background The risk of falls is a global public health issue, with over 38 million disability-adjusted life years lost annually due to falls. However, older adults with mild cognitive impairment (MCI) are more likely to fall and suffer more severe injuries compared to cognitively normal older adults, which also has an impact on their quality of life. Methods This study was a randomized, controlled trial with two parallel groups, allocated in a 1:1 ratio using a concealed allocation mechanism and assessor blinding. 53 participants were randomly assigned to the 12-week Wuqinxi exercise group or the 12-week stretching exercise group. Overall cognitive function, risk of falls, and quality of life were assessed at baseline and at post. Independent t-tests and non-parametric tests were used to compare the outcome variables between the two groups. Results There were no significant differences in baseline demographic characteristics or assessment indicators between Wuqinxi exercise group and stretching exercise group (P > 0.05), indicating comparability between the groups. After 12 weeks of intervention, the Wuqinxi exercise group showed significant improvements in primary outcome measures, including cognitive function and risk of falls (P < 0.001). In the SF-12 quality of life, Wuqinxi exercise group showed statistically significant improvements in six dimensions (P < 0.05), including general Health (GH), physical Function (PF), role Physical (RP), body Pain (BP), role Emotional (RE), and mental Health (MH). In two dimensions insignificant vitality (VT, P = 0.649) and social function (SF, P = 0.089). The median and interquartile range after intervention were also overall better in the Wuqinxi exercise group. In addition, the Mini-Mental State Examination (MMSE) was significantly negatively correlated with Timed Up and Go TestTimed Up and Go Test (TUG) (r = −0.52, p < 0.01) and significantly positively correlated with Modified Falls Efficacy Scale (MFES) (r = 0.463, p < 0.05). The improvement in quality of life in the BP and SF dimensions was significantly positively correlated with the increase Montreal Cognitive Assessment (MoCA) and MMSE respectively (BP-MoCA: r =  0.406, p < 0.05; SF-MMSE: r = 0.399, p < 0.05). Conclusion The Wuqinxi exercise is a feasible and acceptable intervention for improving cognitive function, preventing falls, and enhancing quality of life in older adults with MCI. Our study’s findings emphasize the importance of Wuqinxi exercise in older adults’ health management and confirm the feasibility of a large-scale andomized controlled trial.